Six new species of the Oriental genus Hlavaciellus Jałoszyński (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2021)
Six new species of the cephenniine genus Hlavaciellus Jałoszyński are described: H. cincinnalis sp. n. (Malaysia: Sabah); H. carinatus sp. n. (Malaysia: Pahang); H. microtuberculatus sp. n. (Malaysia: Pahang); H. diversipilosus sp. n. (Malaysia: Pahang); H. concavus sp. n. (Indonesia: Sumatra); and H. sumatranus sp. n. (Indonesia: Sumatra). An updated key to identification of males of all nominal species of Hlavaciellus is given.